A presunção de constitucionalidade das leis regulatórias e econômicas na jurisprudência do Supremo Tribunal Federal - Arigony, Alexandre Foch (2019)
The presumption of constitutionality determines the relative presumption of constitutionality in favor of all laws of the legal system. Part of the doctrine holds that this presumption must be graded at levels according to the subject matter of the law. Thus, the presumption is weaker in relation to laws that restrict fundamental rights and stronger in relation to laws dealing with regulatory and economic issues (lato sensu regulation). This dissertation examines how the presumption of constitutionality is treated by the legal system and how the Brazilian Supreme Federal Court judges the constitutionality of economic and regulatory laws. The research problem is to verify the strength of the presumption of constitutionality (or degree of deference) of regulatory and economic laws in the jurisprudence of the Brazilian Federal Supreme Court. The hypothesis is as follows: the Brazilian Federal Supreme Court attributes a strong presumption of constitutionality to regulatory laws. This strong presumption of constitutionality can also be seen in the quantitative analysis of the regulatory and economic laws that have had their constitutionality challenged. This work is justified by contributing to the attempt to verify how the Brazilian Federal Supreme Court behaves in regulatory and economic demands. The methodology used was bibliographic research and empirical study of arguments and results of 79 abstract actions judged by the Brazilian Federal Supreme Court in a period of 30 years, from 1988 to 2018.